Destiny - Adenike, Juliana (Nigeria, 2021)
The story depicts the agonies of the barren and likewise the joys of motherhood. It is a story of African roots, a tale showing the complexity of being a woman in a non-conforming culture. The story is centered on love, trust, resilience and anger...
Keywords: Juvenile Fiction; Women